Friction Force Analysis of Multi Axles Train Bogie System Using 3d Finite Element Model - Weast, Ericson Samuel Bentai; Wahab, Md Saidin (Research Progress in Mechanical and Manufacturing Engineering, 2024)
There are several components of the train that are crucial to the passengers' safety and comfort. The bogie is one of the most crucial parts of a railroad train. The bogie is crucial to safe railroad operation because it securely holds the railcar body, maintains stability on both straight and curved tracks, and provides smooth riding. There are many kinds of bogie systems, but the focus of this study is on the analysis of the friction forces in multi-axle train bogie systems. Two railroads are utilized in the simulation. The axle load was calculated using information from previous bogie systems. The simulation's displacement, velocity, and acceleration data were recorded. The graph compares all the tabulated data. The result shows that there were no derailment issues when the speed hits maximum threshold.